Предмет: Математика,
автор: Аноним
восстанови выражение (х-2)²=(х+(-2х))² учи ру
Ответы
Автор ответа:
1
Ответ:
ВООО
ДЕРЖИ
Пошаговое объяснение:
х²-2х=х+2-х²,
х²-2х-х-2+х²=0,
2х²-3х-2=0.
D=b²-4ac= (-3)²-4·2·(-2)=9+16=25
x=(3-5)/4=-1/2 или х =(3+5)/4=2
Ответ. -1/2 ; 2
gromte2010:
ЭТО ОТВЕТ
Похожие вопросы
Предмет: Химия,
автор: lianka9591
Предмет: Математика,
автор: timoha898
Предмет: Математика,
автор: haykazpetrosya
Предмет: Химия,
автор: nastenkaemtseva
Предмет: Математика,
автор: ArinA1111115555